Cosmological tensions: current status and future perspectives - Graef, Leila L. (Cadernos de Astronomia, 2024)
In recent years, a growing discrepancy (tension) in the values of important cosmological parameters when inferred through different observations has been reported in the literature. In addition to being a possible indication of problems in the Standard Model of Cosmology, or in the analysis of observational data, the tension calls into question the consistency of certain procedures typically adopted in cosmology. The problem of tension in the Hubble constant H0 is considered by many to be one of the most pertinent problems in current cosmology, and it is related to a second problem, the tension in the parameter σ8, associated with the amplitude of linear fluctuations of the matter. Here we will discuss some of the reasons why this problem has achieved such relevance, being responsible for a large part of the efforts in modern cosmology. A brief overview of the main scenarios that have been considered in an attempt to address such problems from the point of view of cosmology will also be presented. The main challenges and future perspectives in this direction will also be discussed.